Transcriptomics-based anti-tuberculous mechanism of traditional Chinese polyherbal preparation NiuBeiXiaoHe intermediates - Nan Wang; Qianqian Ma; Qianqian Ma; Junxian Zhang; Jie Wang; Xiaojun Li; Yan Liang; Xueqiong Wu (Frontiers Media S.A., 2024)
BackgroundIntegrated traditional Chinese medicine and biomedicine is an effective method to treat tuberculosis (TB). In our previous research, traditional Chinese medicine preparation NiuBeiXiaoHe (NBXH) achieved obvious anti-TB effects in animal experiments and clinical practice. However, the action mechanism of NBXH has not been elucidated.MethodPeripheral blood mononuclear cells (PBMCs) were collected to extract mRNA and differentially expressed (DE) genes were obtained using gene microarray technology. Finally, GEO databases and RT-qPCR were used to verify the results of expression profile.ResultAfter MTB infection, most upregulated DE genes in mice were immune-related genes, including cxcl9, camp, cfb, c4b, serpina3g, and ngp. Downregulated DE genes included lrrc74b, sult1d1, cxxc4, and grip2. After treatment with NBXH, especially high-dose NBXH, the abnormal gene expression was significantly corrected. Some DE genes have been confirmed in multiple GEO datasets or in pulmonary TB patients through RT-qPCR.ConclusionMTB infection led to extensive changes in host gene expression and mainly caused the host's anti-TB immune responses. The treatment using high-dose NBXH partially repaired the abnormal gene expression, further enhanced the anti-TB immunity included autophagy and NK cell-mediated cytotoxicity, and had a certain inhibitory effect on overactivated immune responses.